COGNITIVE IMPROVEMENT OF STUDENTS IN WRITING DESCRIPTIVE TEXTS THROUGH THE PJBL MODEL - Rahimah; Siti Mayang Sari; Akmaluddin; Lili Kasmini (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study explores students' cognitive improvement in writing descriptivetexts through PjBL. The research was conducted by involving 50 students asresearch subjects. Data were collected through written tests before and after theimplementation of PjBL and questionnaires on student perceptions of learningthrough PjBL. The results showed a significant increase in students' ability towrite descriptive texts after participating in PjBL learning. Through concreteprojects involving students in gathering information, analyzing data, andcommunicating their findings in descriptive texts, students develop cognitiveskills such as critical thinking, problem-solving, and better-organizinginformation. In addition, students also give positive perceptions of learningthrough PjBL. They feel engaged and motivated and enjoy interactive, projectbased learning experiences. This shows that PjBL can create a positive learningenvironment and increase student motivation and participation in learningactivities. This research has important implications for the development oflearning to write descriptive texts at SMPN 2 Peukan Bada. The PjBL modelcan be used as an effective alternative in improving student's writing skills andpromoting the cognitive skills needed in the writing process. Recommendationsfor further research are to involve a more comprehensive sample and conductcomparative studies with other learning methods to strengthen the findings ofthis study. Thus, this study makes a significant contribution. They understandthe importance of PjBL in improving students' cognitive writing in descriptivetexImplementing PjBL is expected to be an effective and innovative learningstrategy in improving students' writing skills, positively impacting the learningprocess at SMPN 2 Peukan Bada.